A computational model of a norm's yield - Itaiwi A.-M.K.; Ahmad M.S.; Tang A.Y.C.; Mahmoud M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computation theory; Computational methods; Robotics; Computational model; Mining algorithms; norm benefits; norm yield; Normative agents; Norms detections; Reasoning ability; Multi agent systems